The Influence of Work Mutations, Workplace Environment on Work-Life Balance, Work Motivation and Employees Performance at The Technical Implementing Unit (UPT PPD) of Regional Revenue Agency East Java Province - Jauhar, Alfian; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The regional development carried out demands an increase in the revenue of Regional Original Revenue (PAD) every year and an increase in the performance of the employees of the Regional Revenue Agency as a Regional Apparatus Organization (OPD) producing PAD. The author's objective is to determine the impact of workplace environment and work mutations on work life balance, employee motivation and performance on the job. This study's population consisted of UPT PPD Regional Revenue Agency of East Java Province employees. There were as many as 110 employees sampled. The method of Structural Equation Modeling (SEM) is employed as the analytical tool. The findings of this study reveal that work mutations have an effect on work life balance, there is an effect of work mutations on job motivation. alterations in the workplace have an effect on employee performance, there is a relationship between the workplace environment and work life balance, the workplace environment has an impact on employee motivation, there is no effect of the workplace environment on employee performance, however work life balance does have an effect on employee performance, there is no relationship between work motivation and employee performance, and work-life balance has no effect on job motivation.